2020
DOI: 10.7717/peerj.9131
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide sequence identification and expression analysis of ARF family in sugar beet (Beta vulgaris L.) under salinity stresses

Abstract: Auxin response factor (ARF) proteins respond to biological and abiotic stresses and play important roles in regulating plant growth and development. In this study, based on the genome-wide database of sugar beet, 16 BvARF proteins were identified. A detailed investigation into the BvARF family is performed, including analysis of the conserved domains, chromosomal locations, phylogeny, exon-intron structure, conserved motifs, subcellular localization, gene ontology (GO) annotations and expression profiles of Bv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…The functions of ARFs have been studied in Arabidopsis thaliana , tomato ( Solanum lycopersicum ), papaya ( Carica papaya L.), sugar beet, peach, and other plant species [ 13 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 ]. AtARF 2 , 3 , 5 , 6 , 7 , 8 , 17 , and 19 regulate apical bud formation, pollen wall synthesis, vascular bundle development, hypocotyl tropic movement, and adventitious root formation [ 26 , 27 , 28 , 29 , 30 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The functions of ARFs have been studied in Arabidopsis thaliana , tomato ( Solanum lycopersicum ), papaya ( Carica papaya L.), sugar beet, peach, and other plant species [ 13 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 ]. AtARF 2 , 3 , 5 , 6 , 7 , 8 , 17 , and 19 regulate apical bud formation, pollen wall synthesis, vascular bundle development, hypocotyl tropic movement, and adventitious root formation [ 26 , 27 , 28 , 29 , 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…Soil salinization is one of the most crucial abiotic stresses that affects the growth of plant leaves, roots, and stems [ 37 ]. Various ARF genes act in response to salinity stress in some plants, such as sugar beet ( Beta vulgaris L.), tomato ( Solanum lycopersicum ), rice ( Oryza sativa ), sweet potato, and Tamarix chinensis [ 19 , 38 , 39 , 40 , 41 , 42 , 43 ]. It has been reported that many SlARFs were differentially expressed in tomato leaves and roots under salt stress conditions, and all SlARF genes were down–regulated in leaves except SlARF1 , SlARF4 , and SlARF19 , whose expression was significantly induced [ 38 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…31 Apple ( Malus pumila ) ARF genes have been identified in apple [ 12 ]. In addition, most BvARF genes were found to be strongly responsive to salt stress [ 13 ]. Research in Sorghum showed that the SbARF genes are mainly down-regulated under salt stress in the root, and most SbARF genes show significant down-regulation under drought stress, and the expression of three genes ( SbARF10,16 and 21 ) was significantly up-regulated [ 14 ].…”
Section: Introductionmentioning
confidence: 99%